The Relationship Between Perceived Difficulty, Reading Perceptions, and Critical Reading Strategy: A Lesson from EFL University Students - Samsudin, Samsudin; Asbar, Asbar; Jazadi, Iwan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Critical reading is central to academic literacy in EFL higher education, yet many students struggle to engage strategically with complex academic texts. While prior research has examined reading strategies extensively, empirical attention has been limited to how perceived Difficulty and reading perceptions jointly relate to the use of critical reading strategies in Indonesian university contexts. This study adopted an explanatory sequential mixed-method design involving 32 Indonesian EFL undergraduate students. Quantitative data were collected using a four-point Likert-scale questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple regression. The quantitative phase was followed by semi-structured interviews to explain and contextualize the statistical patterns. The findings indicate that students generally reported high levels of strategy use and positive perceptions of reading, while perceived Difficulty remained moderate. Correlation results showed that reading perception was moderately associated with strategy use, whereas perceived Difficulty demonstrated weak relationships. Although the regression model did not reach statistical significance, reading perception displayed a marginal predictive tendency, suggesting that students’ epistemic orientation toward reading may play a more meaningful role than perceived textual challenge in shaping strategic engagement. Qualitative findings further revealed that students conceptualize Difficulty as multidimensional, encompassing workload, time constraints, motivation, and contextual relevance, rather than merely linguistic complexity. This study suggests that fostering positive perceptions of reading may be more pedagogically impactful than focusing solely on reducing textual Difficulty. The findings contribute to theoretical discussions of the affective–cognitive dimensions of critical reading and offer practical implications for designing strategy-oriented instruction in EFL higher education.